2013
DOI: 10.1021/ja405911h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Organophosphate Hydrolysis Activity from a Weak Promiscuous Lactonase Template

Abstract: Rapid evolution of enzymes provides unique molecular insights into the remarkable adaptability of proteins and helps to elucidate the relationship between amino acid sequence, structure and function. We interrogated the evolution of the phosphotriesterase from Pseudomonas diminuta (PdPTE), which hydrolyzes synthetic organophosphates with remarkable catalytic efficiency. PTE is thought to be an evolutionarily “young” enzyme and it has been postulated that it has evolved from members of the phosphotriesterase-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 40 publications
2
40
0
3
Order By: Relevance
“…Experiments lend credence to the proposal that promiscuity underlies much of enzyme innovation. Numerous studies have shown that an enzyme optimized for one reaction can adapt under laboratory mutation and screening/selection to take on the function of a different member of the superfamily, sometimes with efficiency that rivals nature's solutions (Aharoni et al 2005;Gerlt & Babbitt, 2009;Meier et al 2013).…”
Section: Nature's Approach To Chemical Innovationmentioning
confidence: 99%
“…Experiments lend credence to the proposal that promiscuity underlies much of enzyme innovation. Numerous studies have shown that an enzyme optimized for one reaction can adapt under laboratory mutation and screening/selection to take on the function of a different member of the superfamily, sometimes with efficiency that rivals nature's solutions (Aharoni et al 2005;Gerlt & Babbitt, 2009;Meier et al 2013).…”
Section: Nature's Approach To Chemical Innovationmentioning
confidence: 99%
“…However, as Nobeli et al [11] had pointed out, such results lay the foundation of subsequent efforts using protein engineering/ directed evolution to improve upon these catalytic activities. Large number of successful results which prove this are already available in the literature [12,[71][72][73].…”
Section: Catalytic Promiscuity: Beyond Lipasesmentioning
confidence: 76%
“…We characterized several such mutants with broader stereo-specificity and also with different leaving groups, which could be used for the in vivo detoxification of real nerve agents. These in vivo prophylactic activity of evolved variants and the newly developed screens provide the foundation for designing PON1 and other OP degrading enzymes for prophylaxis against other G-type agents [3,43].…”
Section: Applications Of Promiscuous Functionsmentioning
confidence: 99%